Pengembangan Sistem Peminjaman Peralatan Praktik Laboratorium Plumbing Berbasis Website pada Program Studi Pendidikan Teknik Bangunan Universitas Negeri Jakarta - Selvy Windy Lestari; Anisah; Arris Maulana (INDO PUBLISHING, 2025)
The current equipment borrowing process in the laboratory is still carried out manually using pre-prepared forms sheet. This manual process certainly has its drawbacks and requires a more modern, effective, and efficient equipment borrowing system. The proposed solution is the development of a web-based Laboratory Equipment Borrowing System. This system is expected to serve as an alternative to assist the data recording process and simplify as well as accelerate the borrowing process by leveraging digital technology. The resulting product in this study is an online-accessible platform called “LabLend Plumbing PTB”. The research method used in this study is Research and Development (R&D), employing the 4D model (Define, Design, Develop, Disseminate). Meanwhile, the system development method follows the Waterfall model, consisting of five stages: Analysis, Design, Implementation, Testing, and Maintenance. Based on the research results, the media expert validation obtained a score of 0,78 which falls into the “High” validity category. Meanwhile, the limited trial assessment conducted by the Building Engineering Education laboratory staff at the State University of Jakarta as users yielded a score of 89%, also categorized as “Highly Eligible.”